2022
DOI: 10.1186/s12903-022-02363-3
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal and dentoalveolar effects of class II malocclusion treatment using bi-maxillary skeletal anchorage: a systematic review

Abstract: Background The goal of this systematic review was to assess the available evidence regarding the skeletal and dentoalveolar effects of bi-maxillary skeletal anchorage devices (BMSADs) used in treating growing class II malocclusion patients. Methods A comprehensive search was conducted on PubMed, Scopus, Science Direct, Web of Science, Cochrane, and LILACS up to November 2021, which was augmented by a manual search. The studies included were clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
(177 reference statements)
0
3
0
Order By: Relevance
“…Fortunately, Class II elastic traction is a biomechanical solution counteract incisor proclination during molar distalization by exerting a retraction force on upper anterior teeth [16,17]. However, the biomechanical superiority of the two traction modes (canine precision cut vs. canine button) is yet to be determined [14,18]. Moreover, although the predictability of molar distalization at the distalization stage was as high as 88%, it dropped down to 42% following anterior retraction [11,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, Class II elastic traction is a biomechanical solution counteract incisor proclination during molar distalization by exerting a retraction force on upper anterior teeth [16,17]. However, the biomechanical superiority of the two traction modes (canine precision cut vs. canine button) is yet to be determined [14,18]. Moreover, although the predictability of molar distalization at the distalization stage was as high as 88%, it dropped down to 42% following anterior retraction [11,19].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, upper molar distalization, achieved by "pushing" force exerted on molars, is one of the most predictable tooth movements with clear aligner [12,13]. However, labial movement of anterior teeth occurs during molar distalization due to its reciprocal force, posing periodontal threats to those with inadequate periodontal support [14,15]. Fortunately, Class II elastic traction is a biomechanical solution counteract incisor proclination during molar distalization by exerting a retraction force on upper anterior teeth [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] However, these designs limited the use of miniplates only on mandibular symphysis and failed to provide substantial evidence to prove the superior skeletal effects attained. 7,8 A recent systematic review 9 also concluded that FFA supported by bi-maxillary anchorage failed to control the proclination of mandibular incisors.…”
Section: Introductionmentioning
confidence: 99%